The notional and pragmatic components of literal, figurative, and/or transferred meaning of phrasemes - KŘIVANCOVÁ , Michaela (Bohemistyka, 2020)
This paper examines the notional and pragmatic components of the meaning of the Czech phrasemes containing names of fairy-tale creatures. We do not aim for exhaustive evidence of phrasemes from thematic unit Names of fairy-tale creatures, but we are trying to prove on a few concrete examples that phrasemes 1) can solely convey literal meanings (either notional or pragmatic, or both notional and pragmatic), or, 2) in addition to verbatim meaning, they can also acquire figurative and/or transferred meaning (namely notional, or pragmatic, or both national and pragmatic concurently). In this paper, we prove that the traditionally postulated concept of Czech phraseology does not apply, namely that each phrasemes is represented by both (a notional and a pragmatic) component of meaning. On the contrary, it appears that some phraseological units can only be of notional significance, other phrasemes can only have pragmatic significance.